Decision Support System Using the Method Analitychal Hierachy Process for Achieved Student Assessment - Ahmad Khumaidi (Journal of Intelligent Business and Technology Science (JIBTec), 2022)
Decision-making in an institution or school is very important. The principal should make a decision based on calculations and long-term thinking so that decisions that determine student academic achievement to be taken is not wrong. In Kebumen Islamic Junior High School there are still problems in making student learning report, to determine the achieving students only determined using report score, the absence of optimal utilization of data report assessment of student learning outcomes, there is still difficult to know the achievement of student learning activities. Using the AHP method can make it easier for teachers to determine the academic achievement of students precisely and quickly, where the AHP method is one of the methods used to solve decision support systems. Analytical Hierarchy Process provides convenience by providing multiple criteria with a framework of thinking that konferhensif consideration of hierarchy process which then carried out weighting with each criterion in determining the eligibility of student achievement election.